2017
DOI: 10.7554/elife.28974
|View full text |Cite
|
Sign up to set email alerts
|

Direct modulation of aberrant brain network connectivity through real-time NeuroFeedback

Abstract: The existence of abnormal connectivity patterns between resting state networks in neuropsychiatric disorders, including Autism Spectrum Disorder (ASD), has been well established. Traditional treatment methods in ASD are limited, and do not address the aberrant network structure. Using real-time fMRI neurofeedback, we directly trained three brain nodes in participants with ASD, in which the aberrant connectivity has been shown to correlate with symptom severity. Desired network connectivity patterns were reinfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 61 publications
3
68
0
Order By: Relevance
“…Despite increasing interest in the application of rt- fMRI, only a few studies to date have directly evaluated effects of NFT on functional connectivity between brain regions [54, 56, 71, 76-79]. In line with the present findings, a previous study with a relatively small sample of healthy subjects revealed initial evidence for the feasibility of connectivity-informed NF which was associated with increased perception of positive valence stimuli.…”
Section: Discussionsupporting
confidence: 79%
“…Despite increasing interest in the application of rt- fMRI, only a few studies to date have directly evaluated effects of NFT on functional connectivity between brain regions [54, 56, 71, 76-79]. In line with the present findings, a previous study with a relatively small sample of healthy subjects revealed initial evidence for the feasibility of connectivity-informed NF which was associated with increased perception of positive valence stimuli.…”
Section: Discussionsupporting
confidence: 79%
“…Despite increasing interest in the application of rt-fMRI only a few studies to date have directly evaluated effects of neurofeedback training on functional connectivity between brain regions (50,(63)(64)(65)(66)(67)(68). In line with the present findings, a previous study with a relatively small sample of healthy subjects revealed initial evidence for the feasibility of connectivityinformed NF which was associated with increased perception of positive valence stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, what sort of target can people learn to attain? For instance, while some evidence suggests that people can learn to modulate brain connectivity (Koush et al, 2015;Ramot, Grossman, Friedman, & Malach, 2016;Ramot et al, 2017;Ruiz et al, 2014) or even particular transient spatially extended patterns (Diaz Hernandez et al, 2016), and real-time as well as temporally non-local properties of brain activity | 1463 PAPO there is as yet no clear indications as to the range of feasible NF targets, and questions such as whether or not the measure of brain activity needs to be unique ought to be addressed in earnest. One may conjecture that almost any target may be attainable, so long as it can be expressed in a convenient way, though ultimately the essential ingredient is that cognitive control be able to move brain dynamics to the desired functional regime.…”
Section: Concluding Remark Smentioning
confidence: 99%